Guest edited collection serological study of SARS-CoV-2 antibodies in japanese cats using protein-A/G-based ELISA - Ichiro Imanishi; Ryota Asahina; Shunji Hayashi; Jumpei Uchiyama; Masaharu Hisasue; Masahiro Yamasaki; Yoshiteru Murata; Shigeru Morikawa; Tetsuya Mizutani; Masahiro Sakaguchi (BMC Veterinary Research, 2022)
Abstract Background Little is known about the epidemic status of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in cats in Japan due to insufficiently reliable seroepidemiological analysis methods that are easy to use in cats. Results We developed a protein-A/G-based enzyme-linked immunosorbent assay (ELISA) to detect antibodies against SARS-CoV-2 in cats. The assay was standardized using positive rabbit antibodies against SARS-CoV-2. The ELISA results were consistent with those of a conventional anti-feline-immunoglobulin-G (IgG)-based ELISA. To test the protein-A/G-based ELISA, we collected blood samples from 1,969 cats that had been taken to veterinary clinics in Japan from June to July 2020 and determined the presence of anti-SARS-CoV-2 antibodies. Nine cats were found to have SARS-CoV-2 S1-specific IgG, of which 4 had recombinant receptor-binding domain-specific IgG. Of those 9 samples, one showed neutralizing activity. Based on these findings, we estimated that the prevalence of SARS-CoV-2 neutralizing antibodies in cats in Japan was 0.05% (1/1,969 samples). This prevalence was consistent with the prevalence of neutralizing antibodies against SARS-CoV-2 in humans in Japan according to research conducted at that time. Conclusions Protein-A/G-based ELISA has the potential to be a standardized method for measuring anti-SARS-CoV-2 antibodies in cats. The infection status of SARS-CoV-2 in cats in Japan might be linked to that in humans.